Oral Syphilis : A Case Report - S Padmashree; Nillofer R Halim (Wolters Kluwer Medknow Publications, 2007)
Sexually transmitted diseases are posing a growing public health problem on a global and national scale. Clinicians are increasingly likely to come across associated oral manifestations. We present a case of oral mucosal lesion caused by syphilis. The purpose of the report is twofold: To focus attention on syphilis as arising problem for the dental profession hence attention should be paid to all suspicious lesions and to stress the seriousness of these illnesses and steps that have to be undertaken immediately and deliberately to prevent a pandemic of STDs in our country.